Quarrelsomeness in the workplace: An exploration of the interpersonal construct within the organizational context. (February 2014) - Albert, Lumina S.; Moskowitz, D. S.
We identify "quarrelsomeness" as an important component in understanding destructive behaviors in organizational contexts. Quarrelsomeness has been studied both as a personality trait that generalizes over occasions and situations and as a reflection of interpersonal processes that unfold over time in association with event-specific cues. While a variety of studies have documented the role of quarrelsomeness in explaining behavior in interpersonal contexts, a review of the literature revealed few studies explicitly examining the influence of quarrelsomeness in organizational contexts. As work contexts typically involve frequent interpersonal interactions, it is plausible to expect that quarrelsomeness would be an influence on several organizationally relevant issues. The present article examines quarrelsomeness as a trait related to organizational issues such as dysfunctional conflict and workplace aggression, as a behavior that is likely to emerge in association with event-specific cues, and as a moderator of the association between organizational factors and individuals' behavioral responses to these factors. Theoretical and practical implications are discussed.